THE USE OF MOVEMENT IN LEARNING ENGLISH - Fauziah, Nayla Zulfa; Yunita, Sri (IPI Garut Press, 2024)
This research investigates the impact of movement games on students' speaking performance. Employing a qualitative descriptive design, the study was conducted at an Islamic elementary school in Garut with 4th-grade students as participants. Data were collected through observations, students' speaking scripts, and interviews. The findings indicate that movement games significantly increased students' enthusiasm for learning English, improved their pronunciation, and expanded their vocabulary. Thus, movement games are a promising alternative for enhancing students' speaking skills.